Optimasi Penjadwalan Produksi Menggunakan Metode Campbell Dudek Smith (CDS) Dan Metode Nawaz EnscoreHam (NEH) di PT. RPC Indonesia - Mohammad Adjie Irfansah; Fitri Hardiyanti; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Industrial competition in the era of globalization causes every company engaged in manufacturing to continue to develop quality to meet customer satisfaction. PT RPC Indonesia is one of the manufacturing companies engaged in the production of fiberglass, especially in piping components. PT. RPC Indonesia implements a make to order and flowshop production system which has a function to increase production capability and production services by focusing on machine utility and accuracy of production completion to match the set time through scheduling methods.Campbell Dudek Smith (CDS) and Nawaz Enscore Han (NEH) methods are the proposed methods in this research. These two methods will be compared with the company's existing method to determine the best and optimal scheduling method by finding the minimum makespan value. The results of this study show that both methods can be used by companies as alternative scheduling models in minimizing total production time. Scheduling with the CDS method produces a makespan of 3834.15 hours and is 1069.34 hours faster than the existing method. Likewise, the NEH method produces a makespan of 3820.63 hours and is 1082.86 hours faster than the existing method. Based on these criteria, the most recommended method for the company is theNawaz Enscore Ham (NEH) method.